Taxonomic review of the Sebastes pachycephalus complex (Scorpaeniformes: Scorpaenidae) - Kai, Yoshiaki; Nakabo, Tetsuji (Zootaxa, 2013)
A taxonomic review of the Sebastes pachycephalus complex established the existence of two valid species, S. pachyceph-alus and S. nudus. Similarities between them include: cranium armed dorsally with robust preocular, supraocular, postoc-ular, and parietal spines; interorbital space concave; lower jaw lacking scales, shorter than upper jaw; thickened rays in ventral half of pectoral fin; dorsal fin usually with 13 spines and 12 soft-rays; pored lateral line scales 27–35 (usually 29– 33). However, S. pachycephalus is distinguishable from the latter in having minute scales below the entire dorsal-fin spine base (vs. lacking minute scales below first to fifth or variously to the posteriormost spine in the latter), dark spots scattered on the dorsal, anal and caudal fins (vs. no distinct dark spots), and lacking distinct colored markings on the dorsum (vs. yellow or reddish-brown markings present). Although both species occur off the southern Korean Peninsula and in the Bohai and Yellow Seas, in Japanese waters, the former is distributed from northern Honshu Is. southward to southern Ky-ushu Is., whereas the latter extends from southern Hokkaido southward along the Pacific coast of Japan to Kanagawa, and along the Sea of Japan coast to northern Kyushu Is., including the Seto Inland Sea. Sebastes nigricaus, S. nigricans, and S. latus are confirmed as junior synonyms of S. pachycephalus, and S. chalcogrammus as junior synonym of S. nudus, based on the examination of type specimens.